Prognostic impact of AMP-activated protein kinase expression in ovarian carcinoma: Correlation of protein expression and GC/TOF-MS-based metabolomics - Buckendahl, Ann-Christin; Budczies, Jan; Fiehn, Oliver; Darb-Esfahani, Silvia; Kind, Tobias; Noske, Aurelia; Weichert, Wilko; Sehouli, Jalid; Braicu, Elena; Dietel, Manfred; Denkert, Carsten (Oncology reports, 2011)
AMP-activated protein kinase (AMPK) plays a central role in regulating energy metabolism in cells. AMPK activation results in down-regulation of anabolic pathways (e.g., fatty acid biosynthesis) and switches on catabolic processes such as glucose uptake, glycolysis or fatty acid oxidation. Recent studies in cell culture models have shown that the growth of tumor cell lines was inhibited by AMPK activation, but the expression of AMPK in human ovarian tumors has not been reported so far. In this study we investigated AMPK expression in a cohort of 70 ovarian carcinomas, 14 borderline tumors and 5 normal ovaries and linked the protein expression data to Gas chromatography/ time of flight mass spectrometry (GC/TOF-MS) based metabolomics. We observed a significantly higher expression in ovarian carcinomas compared to borderline tumors and normal ovaries (p=0.038). Decreased AMPK expression correlated significantly with higher tumor grade (p=0.009) and was of adverse prognosis in patients with advanced tumor stages (p=0.016) as well as in patients with serous ovarian carcinomas (p=0.037). GC/TOF-MS based metabolomics revealed a significantly higher concentration of glucose in AMPK-negative carcinomas (p=0.022) as well as overexpression of other metabolites from carbohydrate metabolism. Our results indicate a role for AMPK in progression of ovarian tumors and point towards a prognostic impact of AMPK expression for patient overall survival. Furthermore, our data suggest a deregulation of the AMPK-dependent energy metabolism in human ovarian carcinomas. In future clinical studies, activation of AMPK in ovarian carcinoma patients with advanced tumor stages might be an interesting therapeutic approach.
Gesehen am 24.06.2022